Equality Through Differentiation: Opt-Outs and Enhanced Cooperation as Expressions of Sovereignty - Siman, Michael (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
This chapter addresses the equality of Member States in the context of the EU’s internal framework, focusing on legal and factual changes in the founding Treaties, exemptions to primary law, enhanced cooperation, and the potential for suspension of cooperation and termination of membership. The EU’s founding treaties establish a framework of equality among its Member States, while allowing for flexibility through exemptions and special arrangements in primary law. This principle of equality is balanced by provisions that accommodate the unique circumstances of Member States, such as accession exceptions and optout clauses for states that are unwilling to participate in certain policies. Conversely, opt-in clauses enable selective participation in policies of interest; enhanced cooperation mechanisms provide a legal basis for subsets of Member States to advance integration in specific areas without obligating all members. Cooperation within the EU may be suspended when a Member State violates the EU’s principles or obligations, or disrupts its functioning; such actions can trigger infringement proceedings, conditional funding measures, or the Art. 7 Treaty on European Union (TEU) procedure. Provisions for membership termination, as outlined in Art. 50 of the TEU, raise questions regarding the potential application of the rebus sic stantibus clause.